Ultrastable FeCo Bifunctional Electrocatalyst on Se-Doped CNTs for Liquid and Flexible All-Solid-State Rechargeable Zn–Air Batteries - Zhang, Hongwei; Zhao, Meiqi; Liu, Haoran; Shi, Shuangrui; Wang, Zhenhua; Zhang, Biao; Song, Lin; Shang, Jingzhi; Yang, Yong; Ma, Chao; Zheng, Lirong; Han, Yunhu; et al. (Nano letters, 2021)
The rechargeable Zn–air batteries as an environmentally friendly sustainable energy technology have been extensively studied. However, it is still a challenge to develop non-noble metal bifunctional catalysts with high oxygen reduction as well as oxygen evolution reaction (ORR and OER) activity and superior durability, which limit the large-scale application of rechargeable Zn–air batteries. Herein, we synthesized an ultrastable FeCo bifunctional oxygen electrocatalyst on Se-doped CNTs (FeCo/Se-CNT) via a gravity guided chemical vapor deposition (CVD) strategy. The catalyst exhibits excellent ORR (E 1/2 = 0.9 V) and OER (overpotential at 10 mA cm–2 = 340 mV) properties simultaneously, surpassing commercial Pt/C and RuO2/C catalysts. More importantly, the catalyst shows an unordinary stability, that is, is no obvious decrease after 30K cycles accelerated durability test for ORR and OER processes. The small potential gap (0.75 V) represents superior bifunctional ORR and OER activities of the FeCo/Se-CNT catalyst. The FeCo/Se-CNT catalyst possesses outstanding electrochemical performance for the rechargeable liquid and flexible all-solid-state Zn–air batteries, for example, a high open circuit voltage (OCV) and peak power density of 1.543 and 1.405 V and 173.4 and 37.5 mW cm–2, respectively.